PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP DISIPLIN KERJA KARYAWAN DI DINAS TENAGA KERJA DAN PERINDUSTRIAN KOTA SURAKARTA - Cintya Febriana; Hery Sawiji; Tri Murwaningsih (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2021)
The research aims to determine: (1) the influence of leadership on employee work discipline in the Department of Labor and Industry of Surakarta City (2) the effect of compensation on employee work discipline in the Department of Labor and Industry of Surakarta City (3) simultaneous influence of leadership style and compensation on employee work discipline in the Department of Labor and Industry of Surakarta City. The method in this research uses correlational quantitative methods. The population in this study were employees of the Surakarta Department of Labor and Industry with a total of 57 employees. The sampling technique used a saturated sampling with a total 57 employees. The data collection technique used a questionnaire and documentation. The data analysis technique used the prerequisite test and multiple linear regression. The results showes that: (1) there was a significant positive effect of leadership on employee work discipline (tcount 3,614> ttable 2,004), (2) there was a significant positive effect of compensation on employee work discipline (tcount 2,146> ttable 2,004), (3 ) there is a significant positive influence on leadership and compensation simultaneously or together on employee work discipline (Fcount 14.167> Ftable 3.16).